Legal Analysis of Criminal Law Enforcement on Safety in Sailing of Ships Negligent of Standard Operating Procedures in the Perspective of Shipping Law in Indonesia - Dianti, Marizka Putri; Arpangi, Arpangi (UNISSULA Semarang, 2025)
Indonesia is an archipelagic country that has a dense flow in the maritime world with vital sectors that support logistics and economic flows. The high mobility of shipping in Indonesia requires compliance with established safety standards. However, in practice, negligence is still often found in the Standard Operating Procedure (SOP) for shipping safety. Many business actors and ship crews ignore these provisions, increasing the risk of maritime accidents and harming various parties. This condition shows the need for an in-depth study of efforts to enforce criminal law for violations of shipping SOPs. This study uses a juridical-sociological approach, namely combining normative legal studies with observations of social realities in the field. The approach that is the main basis is legislation, accompanied by references to relevant cases. The data used include primary and secondary data, collected through literature studies of laws and regulations, legal literature, and related investigative and investigative documents. The analysis technique used is descriptive-qualitative, in order to explain the relationship between legal norms and practices in their enforcement. The results of the study show that negligence towards shipping SOPs still often occurs, both in terms of technical operational aspects, miscommunication between related parties, and administrative negligence. This shows the still low quality of human resources (HR) in the shipping sector, minimal ongoing coaching, and less than optimal implementation of safety training. Criminal law enforcement is carried out through the involvement of authorized agencies, starting from the investigation and inquiry stages to the trial process. Therefore, there needs to be a systemic solution in the form of improving the quality of HR, strengthening regulations, and strict law enforcement to create an optimal shipping safety culture.